1992
DOI: 10.1002/mar.4220090403
|View full text |Cite
|
Sign up to set email alerts
|

Apparel catalog patronage: Demographic, lifestyle and motivational factors

Abstract: This study was designed to profile catalog shoppers of apparel and to examine their frequency of shopping. Specifically, it focused on the relative importance of consumers' lifestyle, demographic, and motivational factors in catalog shopping patronage. Data from 680 respondents were analyzed. The data indicated a relationship between consumers who shop for apparel from catalogs and some of the variables included in the study. A multiple regression model indicated that when several variables were considered, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 27 publications
3
35
1
1
Order By: Relevance
“…Jasper and Lan 1992;Korgaonkar 1984;Reynolds 1974;Januz 1983;Gillett 1976;Eastlick and Feinberg 1999). Additionally, non functional motives relating to company responsiveness and reputation have been found to influence the choice of shopping mode -from home or in the store (Eastlick and Feinberg 1999).…”
Section: Shopping Motivations and Shopping Orientationmentioning
confidence: 96%
“…Jasper and Lan 1992;Korgaonkar 1984;Reynolds 1974;Januz 1983;Gillett 1976;Eastlick and Feinberg 1999). Additionally, non functional motives relating to company responsiveness and reputation have been found to influence the choice of shopping mode -from home or in the store (Eastlick and Feinberg 1999).…”
Section: Shopping Motivations and Shopping Orientationmentioning
confidence: 96%
“…Since such concerns affect consumer behavior on the Internet, they help to explain why most consumers use the Internet for browsing rather than buying [12,93]. Some researchers suggest that the amount of risk perceived is a major factor in a consumer's deciding whether to shop via a Downloaded by [University of Connecticut] at 13:25 11 April 2015 certain retail channel [19,49,71,86]. Based on this perspective, consumers who perceive less risk on-line than off-line are more likely to switch to on-line channels than risk-laden consumers.…”
Section: Channel-risk Perceptionsmentioning
confidence: 99%
“…Based on previous research we included gender, age, involvement, variety seeking behavior and technophobia as moderators in our model. The impact of gender on buying behavior in an offline environment has been the focus of attention in numerous scholarly papers [Jasper and Lan 1992, Slama and Tashlian 1985, Zeithaml 1985]. Slama and Tashlian [1985] found that women are more involved in purchasing activities and more heavily influenced by personal interactions than men.…”
Section: Structural Definitionmentioning
confidence: 99%